1974
DOI: 10.1139/v74-080
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Spectrum of Methoxyacetonitrile

Abstract: The pure rotational spectrum of methoxyacetonitrile, CH30CH,CN, has been investigated in the 8-40 GHz region. Spectra of thega~rcl~e and trans conformers, with respect to rotation about the 0-CH, bond, have been assigned. The rotational constants for the ground vibrational state are (in MHz) [Traduit par le journal]Can.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

1974
1974
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 3 publications
1
16
1
Order By: Relevance
“…111 addition Hirota concluded that the energy difrere~ice between the two conformers is less than 1 kcal mol-I. In our laboratory it was deterniined that metlioxyacetonitrile, CH,OCH,CN, is predominantly in the gcruclle forni with a small amount of higher energy (by about 1.4 kcal mol-') trails form also present (2). By contrast we found that 3-nietlioxypropio~iitrile, CH,0CH2CH2CN, exists almost entirely as a fi~lly trmls conformer (3).…”
mentioning
confidence: 55%
“…111 addition Hirota concluded that the energy difrere~ice between the two conformers is less than 1 kcal mol-I. In our laboratory it was deterniined that metlioxyacetonitrile, CH,OCH,CN, is predominantly in the gcruclle forni with a small amount of higher energy (by about 1.4 kcal mol-') trails form also present (2). By contrast we found that 3-nietlioxypropio~iitrile, CH,0CH2CH2CN, exists almost entirely as a fi~lly trmls conformer (3).…”
mentioning
confidence: 55%
“…In addition to moving away from the Boltzmann peak of many large molecules at millimeter wavelengths, thus reducing the problem of line confusion (Sutton et al 1984;Crockett et al 2010), the THz window also allows the observation of low-lying torsional or vibrational states. Both methoxyacetonitrile and cyanoethanol have torsional states in the THz window, the lowest one at approximately 93 cm −1 for methoxyacetonitrile (Kewley 1974), and at approximately 108 cm −1 for cyanoethanol (Marstokk & Mollendal 1985). These torsions lie along the path to interconversion between the gauche and anti-conformers for both molecules, and in both cases the gauche and anti-conformers have large but differently oriented dipole moments (Kewley 1974;Marstokk & Mollendal 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Both methoxyacetonitrile and cyanoethanol have torsional states in the THz window, the lowest one at approximately 93 cm −1 for methoxyacetonitrile (Kewley 1974), and at approximately 108 cm −1 for cyanoethanol (Marstokk & Mollendal 1985). These torsions lie along the path to interconversion between the gauche and anti-conformers for both molecules, and in both cases the gauche and anti-conformers have large but differently oriented dipole moments (Kewley 1974;Marstokk & Mollendal 1985). This indicates that these torsional modes should have significant intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations